Indoor microbial contamination and its relation to physical indoor air quality (IAQ) characteristics at different laboratory conditions - A. H., Hazrin; A. A., Anis Syazana; Nordin, Noor Faizul Hadry; A., Norhidayah; Mohd. Aris, Mohd Shukri (Universiti Teknologi Malaysia, 2015)
Laboratory usually refers to a room or building equipped with chemicals and biological agents for scientific experimentation and research. Due to its own indoor hazards and its cause of health implications, it is an urge to assess and to understand the physical indoor air quality (IAQ) characteristics in the laboratory and the variables affecting the degree of exposure to occupants. The main objectives of this study was aimed to assess and to compare the physical IAQ characteristics and airborne pollutants including particulate matters (PM) and gaseous pollutants between laboratories, to identify microbial contaminants via bacterial counts as well as scientific bacterial-kits species identification and to correlate the relationship of physical IAQ characteristics, airborne pollutants and microbial contaminants between different laboratory settings within the same building which are Natural Product (NP) laboratory, Plant Tissue Culture (PTC) laboratory, and Microbiology laboratory. The physical IAQ characteristics and airborne PM was measured using VelociCalc multi-function ventilation meter 9565 and DustMate environmental dust detector respectively. Surface Air System Indoor Air Quality (SAS IAQ) was used to capture the microbial contaminants and after that bacterial counting and identification were done. The scientific method protocol and standard reference limits were compared based on Industrial Code of Practice on Indoor Air Quality (ICOP) (2010) regulated by the Department of Occupational Safety and Health (DOSH). The temperature of PTC laboratory, velocity of NP laboratory and Microbiology laboratory, the respirable particulate matter (PM) of all three laboratories and Colony Forming Unit (CFU) count of PTC and NP laboratory exceeded the standard limit regulated by DOSH. This study demonstrated that Gemella morbillorum is the common bacterial species available in the environment with poor IAQ and there is a significant relationship between physical characteristics, airborne pollutants and microbial contaminants between the different types of laboratory settings. In conclusion, priority should be given to NP laboratory as it is exposed to poor IAQ conditions and immediate action should be taken to eliminate the problems.